2014
DOI: 10.1111/cpf.12218
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic response to resistance exercise with and without blood flow restriction in healthy subjects

Abstract: The LI-BFR session exhibited similar blood lactate to the HI, a higher rating of perceived response than the HI and LI, and equal or lower hemodynamic responses than the HI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
119
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(138 citation statements)
references
References 22 publications
12
119
6
1
Order By: Relevance
“…In another study from our research group, with a similar methodology, haemodynamic differences were not found between exercises with BFR in comparison with exercises with a heavy load but without BFR in a normotensive population (Poton & Polito, ). These results suggest that the population characteristics can influence haemodynamic responses during the exercise.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In another study from our research group, with a similar methodology, haemodynamic differences were not found between exercises with BFR in comparison with exercises with a heavy load but without BFR in a normotensive population (Poton & Polito, ). These results suggest that the population characteristics can influence haemodynamic responses during the exercise.…”
Section: Discussionmentioning
confidence: 55%
“…This point was considered as the blood flow value to be used in the BFR session. The BFR value was based on previous studies of our laboratory (Poton & Polito, ,b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the greater increase in hemodynamics in the LL and LL+BFR groups when compared with the HI group, four studies disagree with our findings Okuno et al, 2014;Poton & Polito, 2016, 2015, and one corroborates with our findings (Araújo et al, 2014). In this context, we observed that the hemodynamics seem to significantly increase the HI protocol when compared with LL or LL+BFR in men.…”
Section: Oxygen Saturation (Spo2)contrasting
confidence: 46%
“…a set number of repetitions) indicating that greater restriction augments the cardiovascular response that occurs during low load knee extension exercise (Rossow et al, 2012). Additionally, previous studies have shown that bilateral knee extension exercise with blood flow restriction does not increase systolic blood pressure (~66%) above traditional high load knee extension exercises (~72%; Poton & Polito, 2015), although the low load blood flow restriction conditions were not performed until volitional failure. Additionally, previous studies have shown that bilateral knee extension exercise with blood flow restriction does not increase systolic blood pressure (~66%) above traditional high load knee extension exercises (~72%; Poton & Polito, 2015), although the low load blood flow restriction conditions were not performed until volitional failure.…”
Section: Discussionmentioning
confidence: 98%